2010
DOI: 10.7205/milmed-d-09-00132
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Mental Health Trends Among U.S. Military Active Duty Personnel: Key Findings From the 2008 DoD Health Behavior Survey

Abstract: The military has shown progress in decreasing cigarette smoking and illicit drug use. Additional emphasis should be placed on understanding increases in prescription drug misuse, heavy alcohol use, PTSD, and suicide attempts, and on planning additional effective interventions and prevention programs. Challenges remain in understanding and addressing military mental health needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(169 citation statements)
references
References 24 publications
3
165
1
Order By: Relevance
“…In the current study, 6% of service members reported past-year suicidal ideation or suicide attempts, whereas 10-12% of respondents reported lifetime or current suicidal ideation in samples of National Guard members and veterans (Calabrese et al, 2011;Guerra et al, 2011). Twelve percent of our U.S. Army sample had PTSD, comparable to previous reports of 11-20% in other military samples (Bray et al, 2010;Hankin et al, 1999;Thomas et al, 2010). Thirty-four percent had depression, which is similar to rates of 23-31% found in other military samples using a version of the CES-D (Hankin et al, 1999;Harbertson et al, 2013).…”
Section: Comorbidity Of Ptsd and Depressionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the current study, 6% of service members reported past-year suicidal ideation or suicide attempts, whereas 10-12% of respondents reported lifetime or current suicidal ideation in samples of National Guard members and veterans (Calabrese et al, 2011;Guerra et al, 2011). Twelve percent of our U.S. Army sample had PTSD, comparable to previous reports of 11-20% in other military samples (Bray et al, 2010;Hankin et al, 1999;Thomas et al, 2010). Thirty-four percent had depression, which is similar to rates of 23-31% found in other military samples using a version of the CES-D (Hankin et al, 1999;Harbertson et al, 2013).…”
Section: Comorbidity Of Ptsd and Depressionsupporting
confidence: 75%
“…More detailed discussion of sampling methods can be found elsewhere (Bray et al, 2009(Bray et al, , 2010. A two-stage sampling method was used.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…These differences included increased rates of past year arrests and DUI rates, but reduced involvement in probation and parole. This is not surprising as literature regarding the military population often highlights the increased risks of substance use disorders among the service members compared to civilians [7].…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, recent estimates indicate that veterans comprise approximately 10% of the nation's total inmate population [5], and that veterans from the Vietnam era are substantially more likely to be involved in the criminal justice system as compared to their civilian counterparts [6]. This is not difficult to imagine as many military members are likely to be facing significant mental health concerns including, anxiety, depression, and PTSD exacerbated by the stress of military life that most civilians do not encounter [6][7][8][9]. And yet, while prior research has shed light on the links between military service and crime, our understanding of the involvement of military personnel in criminal behaviors and the criminal justice system continues to be in its infancy.…”
mentioning
confidence: 97%
“…Recently, it has been suggested that the experiences of military personnel, particularly during combat, might influence their risk-taking behaviors once they return from deployment. This has been an area of significant interest to various military organizations (North Atlantic Treaty Organisation [NATO] Research and Technology Organisation [RTO] Task Group 164, 2012), in light of the growing evidence of increased risk behavior (e.g., substance use or risky driving) and rates of injury post-deployment (e.g., Bray, Pemberton, Lane, Hourani, Mattiko, & Babeu, 2010;Hooper, Debakey, Bellis, Kang, Cowan, Lincoln et al, 2006;Jacobson, Ryan, Hooper, Smith, Amoroso, Boyko et al, 2008;Kelley, Killgore, Athy & Dretsh, 2010;Killgore et al, 2008;Thomsen, Stander, McWhorter, Rabenhorst & Milner, 2011;Zamorski & Kelley, 2012). In one analysis, however, Thomsen et al (2011) observed that the effect of deployment on increased risk behavior was only significant among individuals with a history of engaging in risk behavior.…”
Section: Introductionmentioning
confidence: 99%